Embolisation of Type I Endolic after the Endoprosthesis Replacement of the Infrarenal Aorta. Case Report - M. O. Loginov; A. A. Khamitov; N. R. Chernaya (Креативная хирургия и онкология, 2018)
Introduction. According to the national clinical recommendations, endovascular intervention should be used in the case of infrarenal aneurysm of aorta or common iliac artery in patients with high risk of cardiopulmonary complications during open surgery or serious concurrent conditions. However, despite the reduced risk of minimal invasive intervention, the likelihood of complications remains: the most common of these is endoleak. Type I endoleak is caused by stent graft failure in the area of proximal or distal fixation, leading to an increase of pressure inside the aneurysmal pouch, which can cause it to rupture. In this clinical case, the cause of the endoleak was the short neck of the aneurysm with severe angulation. Leakages of this type must be eliminated by means of a retentive intraluminal cuff or by open surgery. However, the emergency of open surgical intervention in patients with baseline organ dysfunction increases the frequency of complications, often neutralising the advantages of the original endovascular intervention.Materials and methods. The clinical case example demonstrates the effectiveness of embolisation of the endoleak area in a patient with severe cardiac pathology as an alternative to open surgery.Results and discussion. Following elective endovascular implantation of the prosthesis on the control, angiograms are determined by endoleak type I in the area of proximal fixation of endoprosthesis. This is presumably due to incomplete adhesion of endoprosthesis body in the area of the right renal artery. The decision was taken to embolise the zone of leakage. Using a 190.0 cm Abbott Whisper MS 0.014 guide-wire, an Ev3 Rebar-18 2.4F/2.7F. microcatheter was pulled across the area of leakage into the aneurysmatic pouch. An Onyx 18 — 1.5 ml liquid embolic system was pulled through a microcatheter to the area of leakage. Control angiography — embolisation was found to be sufficient. There were no signs of non-target embolisation.Conclusion. If a surgeon is sufficiently experienced and technically capable, type I endoleak embolisation can become a method of choice in the treatment of patients with high-risk open surgery.